El uso beneficioso del libro impreso y del libro digital - Fernández Abad, Francisco Javier (Documentación de las Ciencias de la Información, 2007)
The introduction of information technology in libraries obligate to coexist printed technology and electronic or digital technology. Howere, the impact that electronic publishers produces in this centers, makes that they lay out on the ground the plan of what material is more useful to overtake objectives of different documental unities. It is very important to analyse and to compare the useful use of electronic book and printed book from different perspectives. We study them from diverse points of view, as are the use of information, the book, periodical publishers, storeroom, documental support, juridical regulation, professionals of Documentation or from other more general aspects, they bear to finish that printed technology is more able to diversion literature, study papers, essays as basic manuals; on the contrary, digital technology is more useful to scientific journals and reference works.